1998
DOI: 10.1136/jmg.35.6.502
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and association of an interleukin 4 gene polymorphism with atopic dermatitis in Japanese families.

Abstract: We examined linkage between markers at and near the IL4 gene and atopic dermatitis (AD) in 88 Japanese nuclear families. Affected sib pair analysis suggested linkage between the IL4 gene and AD (SPLINK lod=2.28). Transmission disequilibrium testing showed a significantly preferential transmission to AD offspring of the T allele of the -59OC/T polymorphism of the IL4 gene (p=0.001). A case-control comparison suggested a genotypic association of the TT genotype with AD (odds ratio=1.88, p=0.01). Since the T alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
2
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(109 citation statements)
references
References 17 publications
5
97
2
5
Order By: Relevance
“…In a study done on RA patients, the authors found a weak association of two polymorphisms in the IL-4 gene, the IL-4 −590C/T*T allele and IL-4 intron 3 VNTR repeat 1 {which has been shown to be in tight linkage disequilibrium with +33 C/T SNP in an earlier study (Suppiah et al, 2005)} with susceptibility to the disease (Maksymowych et al, 2002). Existing data from in vitro and in vivo studies (Rosenwasser and Borish, 1997;Kawashima et al, 1998;Cantagrel et al, 1999) suggest that the −590 C/T*T allele which is in tight linkage disequilibrium with the +33 C/T*T allele is associated with increased IL-4 expression. In this present study, there is a significant underrepresentation of the +33 C/T*TT homozygotes in the female patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done on RA patients, the authors found a weak association of two polymorphisms in the IL-4 gene, the IL-4 −590C/T*T allele and IL-4 intron 3 VNTR repeat 1 {which has been shown to be in tight linkage disequilibrium with +33 C/T SNP in an earlier study (Suppiah et al, 2005)} with susceptibility to the disease (Maksymowych et al, 2002). Existing data from in vitro and in vivo studies (Rosenwasser and Borish, 1997;Kawashima et al, 1998;Cantagrel et al, 1999) suggest that the −590 C/T*T allele which is in tight linkage disequilibrium with the +33 C/T*T allele is associated with increased IL-4 expression. In this present study, there is a significant underrepresentation of the +33 C/T*TT homozygotes in the female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Th2 cytokines may have overlapping biological activities (such as IL-4 and IL-13), these cytokines play unique roles in autoimmune diseases as seen in late asthmatic response (Tomkinson et al, 2001) The human IL-4 gene has been mapped to the q arm (5q23-31) of chromosome 5 and is located within a cluster of other cytokine genes (van Leeuwen et al, 1989;Arai et al, 1989). Both in vitro and in vivo studies suggest that the T allele of the +33 SNP (rs2070874; linked to −590 T allele) is associated with increased IL-4 production (Rosenwasser and Borish, 1997;Kawashima et al, 1998;Noguchi et al, 1998). The IL-4R gene is located at 16p11-12.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 In contrast, a large study conducted in 1128 children from Australia and England could not find associations between the C-589T polymorphism and atopic phenotypes, 25 except for a weak association with specific IgE against house dust mites in Australian, but not in English, children. Japanese studies reported linkage between the IL4 promoter polymorphism and atopic dermatitis 9 and asthma 8 in 68 Japanese families. For polymorphism C-33T, a study in 240 Japanese individuals showed a borderline association between the T allele and increased levels of serum IgE.…”
Section: Discussionmentioning
confidence: 99%
“…6 A second single nucleotide polymorphism (SNP; C-33T) was reported recently in the 5′ untranslated region of the gene. 7 Furthermore, an association between C-589T and total serum IgE levels, 6 asthma, 8 and atopic dermatitis 9 was suggested in some studies but could not be confirmed by others. 10 Recently, we have reported a highly significant association of total serum IgE levels with a cluster of 7 tightly linked polymorphisms in the IL13 gene in 3 independent populations.…”
mentioning
confidence: 91%
“…(Figure 1) It was reported that −590T in the promoter region of the IL-4 gene have been related to elevated of serum IgE; this locus has been associated with the diagnosis of asthma in some studies, but not in others. [17][18][19] Burchard et al 20 have showed the association between −590T and asthma severity within the Caucasian population. This SNP is located upstream of all the known control element of IL-4, such as the negative regulatory element, the positive regulatory elements, the NF-Y recognition sequence, the OAP40 recognition sequence, the NF-P recognition sequence, and the TATA box, and affects IL-4 transcription activity.…”
mentioning
confidence: 99%